CLILL: Colombia Leading into Content Language Learning - Rodríguez Bonces, Mónica (Íkala, Revista de Lenguaje y Cultura, 2011)
Content and Language Integrated Learning (CLIL) has been adopted by many nations as a methodology to reach bilingualism. Nonetheless, the implementation of CLIL in Colombia goes beyond teaching a core area in English. It implies a long process, including multiple factors to achieve success. This article presents a general background of the process of bilingualism in Colombia and how different kinds of institutions approach this governmental policy through a critical reflection. The paper presents the challenges when adopting Content and Language Integrated Learning (CLIL) as a strategy to achieve bilingualism. Four key aspects are described to reach the goal of having a bilingual territory: language learning approach, teacher training, development of materials, and cultural and intercultural competence. It is argued that bilingualism may be achieved in the long term by addressing these four aspects when implementing CLIL.